Hubungan Kecemasan Pandemi Covid-19 dengan Pengeluaran ASI Ibu Post Partum di Puskesmas Kedungjajang Kabupaten Lumajang - Inna Ari Mustoifah; Nur Hamim; Iit Ermawati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Postpartum is a period when the mother experiences a change in her role. Self care after delivery is related to nutrition, breastmilk and breastfeeding. COVID-19 can cause illness ranging from mild to severe symptoms. The Pandemic has made postpartum mothers experience anxiety, which can have an impact breastfeeding. The purpose was to determine the relationship between the anxiety of the COVID-19 pandemic and the amount of postpartum mother's breast milk at Kedungjajang Health Center, Lumajang. The design of this study was cross sectional with purposive sampling. The samples were 41 respondents which was carried out on July 2022. This study was questionnaires and observation sheets. The results showed that there were 23 (56.1%) respondents who experienced breast milk not coming out, while the highest proportion of subjects who were having anxiety about COVID-19 pandemic was 25 (61%) respondents. Data processing was using chi square test (p = 0.025). Midwives will further enhance good counseling efforts to individuals and families, especially pregnant women, postpartum mothers and breastfeeding mothers to always think positively and seek information about health, especially Covid-19, so that they are not anxious. Furthermore, the families can increase their role in providing support to mothers so they don't have to have anxiety.